Using digital training to support the wellbeing and management skills of teachers of children with ADHD symptoms - Aldabbagh, Reem (2023)
The current research aim was to determine the feasibility and acceptability of a digital intervention to assist primary school teachers in managing ADHD symptoms in the classroom. The thesis also aimed to provide preliminary evidence of the effectiveness of such digital interventions in decreasing teachers’ stress and enhancing children’s outcomes. The needs of children with ADHD are a significant concern for teachers, with around 5% of children meeting the threshold for clinical diagnosis and an additional 5% of school children having symptoms but not reaching diagnostic threshold. The manifested behaviours of ADHD not only affect the child, but also the teacher and the overall classroom atmosphere.